STRENGTHENING THE ROLE OF UNIVERSITIES AS A MECHANISM OF STATE POLICY FOR THE RE-EMIGRATION OF INTELLECTUAL CAPITAL - Turenko, Vitalii (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
In today’s globalized world, universities play a decisive role in shaping the intellectual potential of the state and in creating conditions for the return of highly qualified specialists with professional experience acquired abroad. The aim and tasks. The aim of the study is to substantiate the role of universities as a key institutional mechanism of state policy aimed at the re-emigration of intellectual capital. The tasks include identifying the main institutional, academic, and infrastructural conditions that ensure the return and effective professional reintegration of highly qualified specialists. Research methods. The study is based on a socio-philosophical and institutional approach, combined with elements of structural-functional and comparative analysis, which makes it possible to consider universities as complex environments for the accumulation, reproduction, and reintegration of intellectual capital. Research results. It is shown that a leading factor in the return of highly qualified specialists is the ability of universities to provide a well-developed research infrastructure that meets the requirements of modern science. The availability of modern laboratories, innovation centers, analytical platforms, electronic resources, and access to global databases creates an environment in which a researcher can realize their scientific potential at a level comparable to that of leading foreign institutions. Discussion. The results indicate that the effectiveness of re-emigration policy depends not only on economic or administrative incentives, but primarily on the quality of institutional academic environments. Universities function not merely as educational institutions, but as complex socio-cultural and research systems that shape the attractiveness of the national academic space for the return of intellectual capital. Conclusions. The capacity of universities to combine research infrastructure, academic culture, international integration, and opportunities for professional development determines the effectiveness of reintegration processes and the sustainability of the state’s intellectual potential in the global knowledge environment.